The media comisive «abuse of a situation of vulnerability» in the crime of human trafficking. Special reference to criminal law in Spain - Benito Sánchez, Demelsa (2020)
This paper analyses one of the means to carry out the conduct of human trafficking as provided by the international legal documents: the abuse of a position of vulnerability of the victim. This controversial expression was initially included in the definition of the crime of the Palermo Protocol against human trafficking to facilitate the ratification of the Protocol by countries with very different legal positions regarding the exercise of prostitution. A broad interpretation of this expression would entail a notable extension of punishable conducts. This is why this paper proposes a restrictive interpretation that equates this means with violent or fraudulent means in which there is no doubt about the absence of consent of the victim.